The use of pyrite to control redox potential to enhance chalcopyrite bioleaching in the presence of Leptospirillum ferriphilum. (1st October 2021) - Hong, Maoxin; Huang, Xiaotao; Gan, Xiaowen; Qiu, Guanzhou; Wang, Jun
Highlights: Adding high ratio pyrite can well control solution redox potential under 370 mV. The maintenance of low redox potential is conducive to chalcopyrite dissolution. Galvanic effect is not the main factor accelerating chalcopyrite dissolution. Pyrite acts as an additional iron source. Abstract: Redox potential (ORP) was proved to be a key factor in promoting chalcopyrite (CuFeS2 ) bioleaching. Though there are some methods for maintaining ORP reported previously, little attention has been given to control it via pyrite. In this work, chalcopyrite bioleaching was investigated in the presence of Leptospirillum ferriphilum ( L. ferriphilum ) with various amounts of pyrite addition. Bioleaching results showed that the addition of pyrite extremely enhanced the dissolution of chalcopyrite, especially when the mass ratio of pyrite and chalcopyrite was 3:1. In this case, ORP was well maintained at an appropriate range (350–370 mV vs. Ag/AgCl) for 25 days. The results of electrochemical tests indicated that the addition of pyrite did not change the electrochemical dissolution mechanism of chalcopyrite. Thus, the effect of pyrite was mainly a redox potential controlling process, and the reduction of chalcopyrite to secondary copper-iron species like chalcocite (Cu2 S) was promoted in the optimum range. Eventually, a high copper extraction (70%) was obtained as a result of the rapid dissolution of formed chalcocite. Based on all the obtained results, a model for illustrating the ORP control of pyrite during chalcopyrite bioleaching in the presence of L. ferriphilum was proposed.